Feasibility study on renewable energy system in tea (Camellia sinensis) estates of North-East India - KUMARI, VANDITA; CHANDRA, HUKUM; ADITYA, KAUSTAV; KUMAR, K RAVI; DASHORA, KAVYA; KRISHNAN, NAVEEN; SANYAL, S; DHARMARAJA, S; KUMAR, SHANTANU (The Indian Journal of Agricultural Sciences, 2021)
The management of energy consumption in agriculture is a worldwide concern because of the adverse effects of CO2 emissions from fossil fuels, which are generally used as an energy source for various applications in agriculture. Renewable energy technologies are promoted in many parts of the world for various agriculture applications for mitigating CO2 emissions associated with fossil fuels. Tea (Camellia sinensis) is the most manufactured beverage consumed in the world and the global tea market has been valued at 15 billion dollars. India ranks second (after China) among the tea producing countries across the World. A pilot study was carried out in the north eastern states of India, which is the major tea-growing region of the country during 2020. The main objective behind study was to explore the use of non-renewable sources of energy and amount of CO2 emission from the conventional energy sources as well as the feasibility of a renewable energy system in tea estates. The results from data analysis reveal that there is huge scope for adoption of renewable energy systems in tea estates of the north-eastern region which will be beneficial both for the tea estates as well as the environment.